Potassium-dependent Changes in the Conformation of the Kv2.1 Potassium Channel Pore - Immke, David (The Rockefeller University Press, 1999)
The voltage-gated K(+) channel, Kv2.1, conducts Na(+) in the absence of K(+). External tetraethylammonium (TEA(o)) blocks K(+) currents through Kv2.1 with an IC(50) of 5 mM, but is completely without effect in the absence of K(+). TEA(o) block can be titrated back upon addition of low [K(+)]. This suggested that the Kv2.1 pore undergoes a cation-dependent conformational rearrangement in the external vestibule. Individual mutation of lysine (Lys) 356 and 382 in the outer vestibule, to a glycine and a valine, respectively, increased TEA(o) potency for block of K(+) currents by a half log unit. Mutation of Lys 356, which is located at the outer edge of the external vestibule, significantly restored TEA(o) block in the absence of K(+) (IC(50) = 21 mM). In contrast, mutation of Lys 382, which is located in the outer vestibule near the TEA binding site, resulted in very weak (extrapolated IC(50) = ∼265 mM) TEA(o) block in the absence of K(+). These data suggest that the cation-dependent alteration in pore conformation that resulted in loss of TEA potency extended to the outer edge of the external vestibule, and primarily involved a repositioning of Lys 356 or a nearby amino acid in the conduction pathway. Block by internal TEA also completely disappeared in the absence of K(+), and could be titrated back with low [K(+)]. Both internal and external TEA potencies were increased by the same low [K(+)] (30–100 μM) that blocked Na(+) currents through the channel. In addition, experiments that combined block by internal and external TEA indicated that the site of K(+) action was between the internal and external TEA binding sites. These data indicate that a K(+)-dependent conformational change also occurs internal to the selectivity filter, and that both internal and external conformational rearrangements resulted from differences in K(+) occupancy of the selectivity filter. Kv2.1 inactivation rate was K(+) dependent and correlated with TEA(o) potency; as [K(+)] was raised, TEA(o) became more potent and inactivation became faster. Both TEA(o) potency and inactivation rate saturated at the same [K(+)]. These results suggest that the rate of slow inactivation in Kv2.1 was influenced by the conformational rearrangements, either internal to the selectivity filter or near the outer edge of the external vestibule, that were associated with differences in TEA potency.